2019
DOI: 10.1101/698910
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Detection of simple and complexde novomutations without, with, or with multiple reference sequences

Abstract: The characterization of de novo mutations in regions of high sequence and structural diversity from whole genome sequencing data remains highly challenging. Complex structural variants tend to arise in regions of high repetitiveness and low complexity, challenging both de novo assembly, where short-reads do not capture the long-range context required for resolution, and mapping approaches, where improper alignment of reads to a reference genome that is highly diverged from that of the sample can lead to false … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 39 publications
(16 reference statements)
0
3
0
Order By: Relevance
“…By characterizing mutation rate variation across the genome and between generations, we may be able to shed light on the impacts of biological processes such as sex and parental age biases. Ultimately, by quantifying the variation in de novo mutation rates across the Tree of Life, we can refine hypotheses regarding the relationship between mutation rates and life history characteristics (Agarwal and Przeworski, 2019;Fazalova and Nevado, 2020;Garimella et al, 2020;Wang et al, 2020;Wu et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…By characterizing mutation rate variation across the genome and between generations, we may be able to shed light on the impacts of biological processes such as sex and parental age biases. Ultimately, by quantifying the variation in de novo mutation rates across the Tree of Life, we can refine hypotheses regarding the relationship between mutation rates and life history characteristics (Agarwal and Przeworski, 2019;Fazalova and Nevado, 2020;Garimella et al, 2020;Wang et al, 2020;Wu et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…This can take two forms: a composite genome containing all the genes found in strains of all lineages and sub-lineages of the MTBC (i.e. both the core and accessory genome) [86], represented as a graph instead of a single sequence [87][88][89][90][91][92], or a selection of reference genomes, with mapping to all or a subset undertaken, as has been done with strains of Mycobacterium chimaera and other pathogens [93,94]. Other authors have also reported that, because of the genetic variability between strains, using a single strain genome as reference genome lacks accuracy [95][96][97].…”
Section: Size Co-ordinates In H37rvmentioning
confidence: 99%
“…is usually represented as a graph instead of a single sequence (Rakocevic et al 2019;Paten et al 2017;Martiniano et al 2019;Marschall et al 2018;Church et al 2015). Alternatively, it can be a selection of reference genomes, with mapping to all or a subset undertaken, as has been done with M. chimaera and other pathogens (van Ingen et al 2017;Garimella et al 2019). Other authors have also reported that because of the genetic variability between strains, using a single strain genome as reference genome lacks accuracy (Ballouz, Dobin, and Gillis 2019;Sherman et al 2019;Li et al 2010).…”
Section: The Classification Of the L5-specific Genes Into Functional mentioning
confidence: 99%